Influence of effective microorganisms (EM) in the composting process rice straw - Che Jusoh, Mohd Lokman (2012)
Rice (Oryza sativa) is a main staple food and also source of carbohydrate in many parts of the world, especially in Asia. In Malaysia, large rice plantation areas are concentrated in west coast mainly in northern area such as Kedah. These large plantation areas yields a large amount of rice straw residue. A major portion of this agricultural waste is disposed by burning or is mulched in rice fields. Serious environmental pollution can occur due to the inappropriate disposal of the waste. In order to add value and to reduce the volume for easier application, composting of rice straw has become increasingly popular. By composting, the properties of the organic matter are easier to handle, more suitable as soil conditioners and organic fertilizer and do not adversely affect the environment. However, composting of rice straw is generally time consuming. Therefore, the application of Effective Microorganisms (EM) to accelerate the maturity and enhance the quality of compost is observed. The objective of this study was to evaluate the effect of EM application on rice straw composting process, nutritional status contents (macro and micronutrients) and also maturity status of the resultant compost. Composting were conducted using mixed raw materials with the ratios of 50% rice straw + 30% goat manure + 20% green waste (vegetables, fruits peels, etc.). There are two treatments in this study that is compost apply with EM and compost without EM (control) using heap methods and were composted for 90 days. The resultant compost were measured for physiochemical determination and also its maturity index. All the parameters measured indicate that, there is a decomposition process occurs on both treatments. The parameters for the temperature, EC and pH shows there is decomposition of organic matter occurs during the 90 days period. The decreased in TOC values and C/N ratio also show organic compound is been consumed by microorganisms. Based on the analysis of certain physical, chemical and biological characteristics of compost obtained by composting rice straw with goat manure and green waste by using EM, it can be concluded that the compost, after 30 days, is very mature and stable compare to compost without EM. The t-test conducted shows that there is significance different between compost apply with EM and compost without EM. The application of EM in compost have increased macro and micronutrients content. The following parameters support this conclusion: compost applied with EM have more N, P and K content (P<0.05) compared to compost without EM. While Fe in compost with EM is much more higher (P<0.05) than compost without EM. Whereas for Zn and Cu, there is no significant difference between treatments. All of the micronutrients (heavy metal’s) values are below the standard limit of heavy metals in compost.